Analisis Unsur Intrinsik Pada Film “Mencuri Raden Saleh” - Yusril Dava Bayu; Annisa Rizqiani; Ida Sakura (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Literary works are creative expressions that focus on the human experience and life, utilizing language as a means of communication. Furthermore, literature is the outcome of human creativity conveyed via the use of writing and language as a means of communication. Literature is essentially a form of artistic expression by humans that use language as a medium to convey experiences, thoughts, feelings, and ideas. Common literary works encountered in daily life include short tales, poems, novels, films, and dramas. The aim of this research is to identify the inherent components contained in the film "Mencuri Raden Saleh". The approach used in this research is to conduct an analytical investigation of a literary work, followed by collecting verifiable evidence. In this analysis, researchers explore the inherent components contained in films, such as topic, characters/characterization, plot, setting, point of view, language style, and message.